Radiotherapy for Geriatric Cancer Patients: Five-year Experience at a North Indian Tertiary Care Hospital - Trivedi, Gaurav; Singh, Sankalp; Lohia, Nishant; S, Harish; Som Vashisth, Rekha; Bisht, Niharika; Viswanath, S; Prashar, Manoj; Tripathi, Garima (Asian Pacific Journal of Cancer Care, 2023)
Background: The incidence of malignancy in elderly population in India has risen due to increased life expectancy, health awareness, and access to tertiary health care. Radiotherapy is the primary treatment modality in elderly cancer patients due to morbidity of surgery. We reviewed and analyzed clinical, disease and treatment profiles of geriatric population treated with conventional radiotherapy at our institute. Methodology: The clinical records of patients aged 70 years or more, treated from January 2015 to December 2019 were analyzed for patient characteristics (age, sex & co-morbidities), disease characteristics (site, histology & stage) and treatment characteristics (modality & intent of treatment, radiation dose). Results: A total of 289 patients aged 70 years and above were treated during the study period. 69% were treated with curative intent, of which, 72.4% received definitive, 24.6% received adjuvant, and 3% received neoadjuvant radiotherapy. 31% were given palliative radiotherapy. The median age was 74.6 years with male: female ratio of 4.25:1. 21.4% of the study patients had co-morbidities. 14% patients were of early stage, 57% locally advanced and 29% had metastatic disease. 51% of the study population received concurrent chemotherapy along with Radiotherapy. 87.1% of those treated with curative intent & 93.3% of patients treated with palliative intent, completed the planned radiotherapy regimen. Out of total 200 patients treated at our institute with Radiotherapy, 187 were prescribed concurrent chemotherapy, while it was exhibited to only 103 patients due to various factors like old age, poor performance status and co-morbidities. Conclusion: Our study showed a high degree of compliance amongst geriatric patients receiving radiotherapy treatment. Toxicity rates in geriatric population were not significantly higher than the overall population treated at our centre. Various factors like disease biology and stage and patient’s performance status, co-morbidities and life expectancy affect the decision making in deciding radiotherapy intent and schedules in cancer patients of geriatric age group. Combined decision making between patients, caregivers and oncologists is crucial in geriatric age group keeping in mind above mentioned factors.